Discarding food vs. starving people: Inefficient and immoral? - Ulrich Koester (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
Intensive discussions about discarding food in recent weeks were prompted by a study commissioned by the German Bundestag and supported by the German Federal Ministry of Nutrition, Agriculture, and Consumer Protection. Spiegel online said on March 13, 2012: Europe's waste would suffice twice to feed the world's hungry. This statement startled many people. Food is discarded in Europe and other prosperous countries while many people in poor countries are starving. Hence, it seems that the global hunger problem could be easily solved. People in rich countries would simply have to deal with food more responsibly. This policy brief critically examines the methodology of identification food loss and the magnitude of estimated quantities and values. Furthermore, it is questioned whether the potential reduction of food loss on one side can really decrease hunger on the other. The paper concludes with a discussion of morals and alternative options for combating hunger. – – In den letzten Wochen wurde intensiv das Wegwerfen von Lebensmitteln diskutiert. Anlass war das Ergebnis einer Studie, die vom Bundesministerium für Ernährung, Landwirtschaft und Verbraucherschutz aufgrund eines Beschlusses des Bundestags gefördert wurde. In Spiegel online wurde am 13.03.2012 festgestellt: Der Abfall Europas würde zweimal reichen, um die Hungernden dieser Welt zu ernähren. Diese Aussage hat viele Menschen erschreckt. In Europa und anderen wohlhabenden Ländern werden Lebensmittel weggeworfen und in den armen Ländern hungern viele Menschen. Es scheint demnach, dass man das weltweite Hungerproblem leicht lösen könnte. Die Menschen in den reichen Ländern müssten lediglich verantwortungsvoller mit Lebensmitteln umgehen. Der vorliegende Beitrag hinterfragt Methodik und Größenordnung der Berechnungen und überprüft, ob verringerte Abfälle auf der einen Seite tatsächlich zu weniger Hunger auf der anderen Seite führen. Abschließend wird auf die Frage der Moral und alternative Möglichkeiten, den Hunger zu bekämpfen, eingegangen.
urn:nbn:de:gbv:3:2-32038
Keywords: 330; Nahrungsmittel; Abfall; Europa; Mangelernährung; Welt